Evaluation of Actual Condition and Planning of Drainage System in Gold Mining at Pit Durian, Site Bakan PT. J Resources Bolaang Mongodow, Lolayan Sub-district, Kotamobagu, North Sulawesi - Dian Kurnia; Rusli HAR; Heri Prabowo (Journals Mining Engineering : Bina Tambang, 2018)
Based on analysis of rainfall data in 2007-2016, rainfall is obtained from the plan of 149,70 mm/day with different rain intensity in each catchment area. 5-year rain recharge period and hydrogeological risk of 67.23%. At the research location, Pit Durian PT. JRBM, in 2017 has 4 catchment areas with different area, total discharge equal to 11.913,206 m3/hour, there are 2 sumps that is South 1 Sump and North Sump with maximum capacity of 12.702 m3 and 29.596 m3 and there is one Volvo KSB LCC-H 200-610 on each sump, there are three open channels and one main setling pond with different compartment capacity. After an evaluation of the mine drainage system in 2017, South 1 Sump requires an additional 2 units of Volvo KSB LCC-H 200-610 and North Sump pumps requiring additional pumps of 1 unit of Volvo KSB LCC-H 200-610 pump.In the planning of Pit Durian mine drainage system in 2018, Pit Durian has 7 catchment areas with different area with total discharge of 14,393,101 m3/hour, there is addition of sump to 5 sump namely South 1 Sump, South 2 Sump, South 3 Sump, North 1 Sump and North 2 Sump with capacity of each sump is planned for 33,485 m3, 40,745 m3, 35,399 m3, 11,565 m3 and 20,193 m3 and requires 1 unit of Volvo KSB LCC-H 200-610 pump on each sump. The of mine drainage system in 2018 is planned to have an open channel as well as a setling pond similar to 2017.